CKII-SIRT1-SM22α loop evokes a self-limited inflammatory response in vascular smooth muscle cells. Issue 10 (16th April 2017) - Shu, Ya-Nan; Dong, Li-Hua; Li, Han; Pei, Qian-Qian; Miao, Sui-Bing; Zhang, Fan; Zhang, Dan-Dan; Chen, Rong; Yin, Ya-Juan; Lin, Yan-Ling; Xue, Zhen-Ying; Lv, Pin; et al.
Abstract: Aims: Sirtuin 1 (SIRT1) inhibits nuclear factor kappa B (NF-κB) activity in response to the inflammatory cytokine tumour necrosis factor alpha (TNF-α). Smooth muscle (SM) 22α is a phosphorylation-regulated suppressor of IKK-IκBα-NF-κB signalling cascades in vascular smooth muscle cells (VSMCs). Sm22α knockout results in increased expression of pro-inflammatory genes in the aortas which are controlled by NF-κB. This study aimed to investigate the relationship between SM22α and SIRT1 in the control of vascular inflammation. Methods and results: The ligation injury model of Sirt1 -Tg/ Sm22α −/− mice displayed an increased level of the inflammatory molecules in the carotid arteries compared with Sirt1 -Tg mice, accompanied with aggravating neointimal hyperplasia. In the in vitro study, on the one hand, we showed that TNF-α induced the epigenetic silencing of SM22α transcription via EZH2-mediated H3K27 methylation in the SM22α promoter region, contributing to inflammatory response. On the other hand, TNF-α simultaneously induced SIRT1 phosphorylation via CKII and thereby protected against inflammation. Phosphorylated SIRT1 interacted with and deacetylated EZH2 and, subsequently, promoted SM22α transcription by inhibiting EZH2 activity. Increased SM22α in turn facilitated the phosphorylation and activation of SIRT1 via recruitment of CKII to SIRT1, which amplified the anti-inflammatory effect of SIRT1. Conclusion: Our findings demonstrate that, in response to TNF-α stimulation, CKII-SIRT1-SM22α acts in a loop to reinforce the expression of SM22α, which limits the inflammatory response in VSMCs in vivo and in vitro . The anti-inflammatory effect of SIRT1 may be dependent on SM22α to some extent. Our data point to targeted activation of SIRT1 in VSMCs as a promising therapeutic avenue in preventing cardiovascular diseases.